Increasing English Vocabulary of Grade VIII Students through Duolingo Application - Maryam; Said, Mawardin M.; Hasyim, Zarkiani; Anggreni, Afrillia (Universitas Islam Ahmad Dahlan (UIAD), 2025)
The purpose of this research is to determine whether the Duolingo application can enhance the English vocabulary of grade VIII students at SMPN 1 Sindue Tombusabora. This research focused on teaching concrete nouns and action verbs, including their spelling, meaning, and use in sentences. A quasi-experimental design was employed, involving two classes: an experimental class (VIII C) and a control class (VIII A), each consisting of 20 students selected through purposive sampling. Data collection was conducted using pretests and posttests to measure changes in vocabulary knowledge before and after the intervention. The experimental class utilized the Duolingo application, while the control class did not receive this treatment. After the posttest, the researcher used statistical analysis to evaluate whether there was a significant difference between the two classes. Based on the data analysis tests, the mean pretest score for the experimental class was 30.62, compared to 35.97 for the control class. After administering the treatment, the mean score on the posttest for the experimental class was 66.45, which is significantly higher than the mean score of 36.96 for the control class. Using a significance level of 0.05, the researcher found that the calculated t-value of 7.50 exceeded the t-value of 1.687 from the t-table. It indicates that the hypothesis was accepted. In other words, grade VIII students at SMPN 1 Sindue Tombusabora can increase their English vocabulary by using the Duolingo application.